The Odyssey - Homer; Fagles, Robert (New York : Penguin Books, 1997)
In the myths and legends that are magnificently retold here, Fagles has captured the energy and poetry of Homer's original in a bold, contemporary idiom, and given readers an "Odyssey" to read aloud, to savor, and to treasure for its sheer lyrical mastery.
Introduction: Spelling and pronunciation of Homeric names -- Maps: Homeric geography : Mainland Greece -- Peloponnese -- Aegean and Asia Minor -- Inset: Troy and vicinity -- Homer: Odyssey : Athena inspires the prince -- Telemachus sets sail -- King Nestor remembers -- King and queen of Sparta -- Odysseus- Nymph and shipwreck -- Princess and the stranger -- Phaeacia's halls and gardens -- Day for songs and contests -- In the one-eyed giant's cave -- Bewitching queen of Aeaea -- Kingdom of the dead -- Cattle of the sun -- Ithaca at last -- Loyal swineherd -- Prince sets sail for home -- Father and son -- Stranger at the gates -- Beggar-king of Ithaca -- Penelope and her guest -- Portents gather -- Odysseus strings his bow -- Slaughter in the hall -- Great rooted bed -- Peace.
"This [pbk.] edition contains minor revisions of the text"--P. 496.
Includes bibliographical references.
Keywords: Odysseus, -- King of Ithaca (Mythological character) -- Poetry; Epic poetry, Greek